2018
DOI: 10.1186/s12978-018-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Are women in Uganda gaining adequate gestational weight? A prospective study in low income urban Kampala

Abstract: BackgroundPre-pregnancy weight and weight gained during pregnancy significantly influence maternal and infant health. Little information is available regarding optimal gestational weight gain (GWG) in relation to pre-pregnancy body mass index (BMI) in Uganda. The study aimed at determining gestational weight gain (GWG) in women pregnant for the first and second time.MethodsThe study was prospective cohort study which included 221 HIV negative women pregnant for the first or second time. It was conducted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The mean total GWG observed in Brazil in 2018 (11.1 kg for all women) is similar to values observed in Mexico (11.7 kg) (Zonana‐Nacach et al, 2010 ) and Uganda (10.6 kg) (Wanyama et al, 2018 ) but lower to that reported from China in 2016 (15.6 kg) (Xiao et al, 2017 ). In a recent study, Carrilho, Farias, et al ( 2020 ) used pooled data from Brazilian studies conducted between 1990 and 2016 and found a mean total GWG of 12.7 kg, which is also close to the mean total GWG observed in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…The mean total GWG observed in Brazil in 2018 (11.1 kg for all women) is similar to values observed in Mexico (11.7 kg) (Zonana‐Nacach et al, 2010 ) and Uganda (10.6 kg) (Wanyama et al, 2018 ) but lower to that reported from China in 2016 (15.6 kg) (Xiao et al, 2017 ). In a recent study, Carrilho, Farias, et al ( 2020 ) used pooled data from Brazilian studies conducted between 1990 and 2016 and found a mean total GWG of 12.7 kg, which is also close to the mean total GWG observed in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…Approximately 22% of all deliveries in the study centre are by caesarean section, of which8 5% are by emergency cesarean section [16]. This high volume combined with the socio-economic challenges [15], poor baseline health status [17,18], and lack of antenatal care [19] experienced by mothers presenting to the hospital, has resulted in high rates of maternal and neonatal morbidity and mortality [20,21]. Studies from this setting have shown that obstetric service provision is not uniform during a 24-h shift cycle [22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, pre-pregnancy BMI was calculated by respondents' height and weight before pregnancy and classified into four groups according to WHO standard criteria (Table 1 ) [ 27 ]. Also, the allowable total weight gain range and rates of weight gain from the beginning of week 13 onwards according to the IOM recommendation is presented in this table [ 28 ]. Women with GWG under the recommended range are considered as inadequate weight gain, those with GWG within the recommended range are regarded as adequate weight gain, and women with GWG above the recommended range are considered as excessive weight gain [ 29 ].…”
Section: Methodsmentioning
confidence: 99%